Experimental study on torsional behavior of spatial main cable for a self-anchored suspension bridge. Issue 14 (October 2019) - Li, Chuanxi; Li, You; He, Jun
In order to understand the torsional behavior of the spatial main cable between two saddles for a self-anchored suspension bridge during the transition process from construction state to completed state, a scaled model (1:15) was prepared and tested. First, the cable anchorage system and cable measurement device were designed. Then, a series of model tests under the conditions of different preloading angles and different tensioning forces for hangers were carried out. Finally, the regularity of the torsional properties was revealed on the basis of the measured twist angle of the main cable. The experimental study shows that the transverse pre-deflected angle of the cable clamp has a decisive influence on the torsional angle of the main cable sections near the cable clamp, but for the main cable sections far from the pre-deflected cable clamp, this influence can almost be negligible. The torsional angle changes linearly within adjacent cable clamps. When inclined angle of the hanger is larger than the pre-deflected angle of the cable clamp, the cable clamp will cause the main cable section to twist in the positive direction, otherwise, the result is reverse. With the increase in the hanger force, the direction of hanger force passes through the cross-sectional center of the main cable, resulting in an unchanged twisting angle. In addition, a three-dimensional finite element model of the test specimen was established and used to analyze the influence of pre-deflected angle of a cable clamp on the torsion angle of the main cable, the same results can be found in finite element analyses in comparison with the test results. Therefore, a reasonable pre-deflected angle of cable clamp can be determined by the finite element model in the primary design state before the construction stage.